Effects of Milling Methods on Rice Flour Properties and Rice Product Quality: A Review - Tian Yu; Sun Jing; Li Jiaxin; Wang Aixia; Nie Mengzi; Gong Xue; Wang Lili; Liu Liya; Wang Fengzhong; Tong Litao (Rice Science, 2024)
High-quality rice flour is the foundation for the production of various rice-based products. Milling is an essential step in obtaining rice flour, during which significant changes occur in the physicochemical and quality characteristics of the flour. Although rice flour obtained through mainstream wet milling methods exhibits superior quality, low production efficiency and wastewater discharge limit the development of the industry. Dry milling, on the other hand, conserves water resources, but adversely affects flour performance due to excessive heat generation. As an emerging powder-making technique, semi-dry milling offers a promising solution by enhancing flour quality and reducing environmental impact. This is achieved by minimizing soaking time through hot air treatment while reducing mechanical energy consumption to reach saturated water absorption levels. However, continuous production remains a challenge. This comprehensive review summarizes the effects of various milling technologies on rice flour properties and product qualities. It also discusses key control indicators and technical considerations for rice flour processing equipment and processes.